2006
DOI: 10.1029/2006gl025811
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean‐monsoon coupled interactions and impending monsoon droughts

Abstract: [1] Monsoon droughts over the Indian subcontinent emanate from failures in the seasonal (June -September) monsoon rains. While prolonged dry-spells (''monsoonbreaks'') pervade on sub-seasonal/intra-seasonal time-scales, the underlying causes for these long-lasting anomalies remain elusive. Based on analyses of a suite of observed data sets, we report an ocean-atmosphere dynamical coupling on intra-seasonal time-scales, in the tropical Indian Ocean, which is pivotal in forcing extended monsoon-breaks and causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 28 publications
1
66
0
Order By: Relevance
“…Anomalously warm SST in the SETIO associated with strong east-west SST gradients favour westerly winds along the equator, which enhance the moisture convergence and convective activity over the SETIO region (Krishnan et al, 2006). GCM simulation experiments suggest that the enhancement of convective activity over the warm SETIO can induce anomalous subsidence over the Indian subcontinent and weaken the monsoon Hadley cell, thereby leading to deficient rainfall over India (Krishnan et al, 2003).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…Anomalously warm SST in the SETIO associated with strong east-west SST gradients favour westerly winds along the equator, which enhance the moisture convergence and convective activity over the SETIO region (Krishnan et al, 2006). GCM simulation experiments suggest that the enhancement of convective activity over the warm SETIO can induce anomalous subsidence over the Indian subcontinent and weaken the monsoon Hadley cell, thereby leading to deficient rainfall over India (Krishnan et al, 2003).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Rajeevan (2001) suggested a similar mechanism for anomalous SST warming in the tropical Indian Ocean associated with the inter-annual variability of high clouds. In addition, Krishnan et al (2006) have recently reported the possibility of a dynamical coupling between the southwest monsoon circulation and the thermocline depth variations in the eastern equatorial Indian Ocean on intra-seasonal timescales. In this dynamical feedback, anomalous westerly winds along the equator push warm water eastward, so as to deepen and warm the surface mixed layer in the eastern equatorial Indian Ocean and also maintain a strong east-west gradient of SST in the equatorial Indian Ocean.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The seasonal mean (JJAS) SST anomalies show significant cooling in southeast Indian Ocean in many IOD years and hence IOD has the potential to influence monsoon. Influence of IOD on monsoon are discussed in detail by previous studies (e.g., Ashok et al 2001Ashok et al , 2004Gadgil et al 2004;Krishnan et al 2006). Here, we consider the cool SST anomalies in the southeastern equatorial Indian Ocean to represent IOD.…”
Section: Modulation Of Extreme Rainfall Events By Indian Ocean Dipolementioning
confidence: 99%